2008
DOI: 10.1002/pros.20819
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐I, insulin‐like growth factor binding protein‐3 and risk of benign prostate hyperplasia in the prostate cancer prevention trial

Abstract: Background We investigated whether peptides involved in cellular proliferation and apoptosis, [insulin-like growth factor I (IGFI) and its major binding protein (insulin-like growth factor binding protein 3)], predicted risk of benign prostate hyperplasia (BPH). Methods We conducted a nested-case control study in the placebo arm of the Prostate Cancer Prevention Trial (PCPT). Cases (n= 727) were men with surgical or medical treatment for BPH; two or more IPSS scores > 14; or two scores of at least five point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 42 publications
0
32
2
5
Order By: Relevance
“…While most other included studies yielded insignificant results, which meant our conclusion was seemingly less robust. Recently, it has been reported that IGFBP3 as a multifunctional anti-proliferative protein gets involved in benign prostatic hyperplasia (BPH) development in a similar way with PCa (Neuhouser et al, 2008;Safarinejad et al, 2011), suggesting that it was possible for some BPH cases to be improperly grouped as controls, not to mention the asymptomatic or underdiagnosed PCa cases. On the other hand, the widely accepted hypothesis that circulating concentration of IGFBP3 runs inversely with PCa risk has been more and more challenged by case-control studies (Severi et al, 1999;Li et al, 2004;Hong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While most other included studies yielded insignificant results, which meant our conclusion was seemingly less robust. Recently, it has been reported that IGFBP3 as a multifunctional anti-proliferative protein gets involved in benign prostatic hyperplasia (BPH) development in a similar way with PCa (Neuhouser et al, 2008;Safarinejad et al, 2011), suggesting that it was possible for some BPH cases to be improperly grouped as controls, not to mention the asymptomatic or underdiagnosed PCa cases. On the other hand, the widely accepted hypothesis that circulating concentration of IGFBP3 runs inversely with PCa risk has been more and more challenged by case-control studies (Severi et al, 1999;Li et al, 2004;Hong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A única diferença estatística encontrada foi com relação à proteína ERK5 que se encontra mais expressa em pacientes com próstatas > 60 gramas em relação às próstatas menores (p=0,019). (Griffiths et al, 1993;Cohen et al, 1994;Steiner, 1995;) e esse importante grupo de peptídeos e seus receptores celulares são encontrados em maiores quantidades nas glândulas com hiperplasia do que em próstatas normais (Gregory et al, 1986; Mori et al, 1990;Steiner, 1995;Neuhouser et al, 2008), e podem estar desencadeando a ativação de KRAS observada em nossos achados.…”
Section: Expressão Das Proteínas E Os Parâmetros Clínicos Dos Pacientunclassified
“…Esses fatores e seus receptores celulares específicos são encontrados em maiores quantidades nas glândulas com hiperplasia do que em próstatas normais e provavelmente orquestram a proliferação celular anormal observada nos casos de HPB (Steiner, 1995;Neuhouser et al, 2008).…”
Section: Influência Dos Andrógenos E Dos Fatores De Crescimentounclassified
See 2 more Smart Citations